Paleogenomic research in the context of modern Biomolecular Archaeology - Dobrovolskaya M.V.; Kunizheva S.S.; Andreeva T.V.; Rogaev E.I. (Вестник археологии, антропологии и этнографии, 2022)
Biomolecular Archaeology is a newly formed field of archaeological science. The 9th International Symposium on Biomolecular Archaeology was held in June 2021 in Toulouse (France) with the participation of almost 500 delegates. Such conferences were originally organized in the beginning of the 21st c. for regular discussion the most relevant topics and the latest achievements in biomolecular archaeology. Thus, the materials of the symposium appear as a representative reflection of the processes taking place in modern science. Paleogenomics being one of the most actively developing components of biomolecular archaeology. The proposed review presents the most striking, in our opinion, reports on the topic, which enables understanding of the potential and prospects of modern paleogenomic research. Conclusions based on the results of paleogenomic studies are crucially important for the study of population formation, which makes it essential to comply with the rules of parity comprehensive research, which have been reflected in the publication of the basic ethical rules for organizing such studies.